PELATIHAN OTOMASI INDUSTRI BERBASIS PROGRAMMABLE LOGIC CONTROLLER (PLC) - Raden Hernadi; Yogi Priyo Istiyono; Sartono Sartono; Siti Fatimatul Zuhro; Said Said; Sumiyati Sumiyati (LPPM Universitas Bina Bangsa, 2024)
The rapid development of technology in the era of industrial revolution 4.0 greatly affects the characteristics of jobs that exist at this time, where skills and competence are the main things that need to be observed. Therefore, the world of education and industry should develop an industry transformation strategy by being able to evaluate the human resource sector that has competence in its field. Answering the challenge as well as the opportunity Muhammadiyah University College A.R. Fachruddin, especially the Faculty of Engineering, is responsible for preparing graduates who are competitive in the industry because they will work in the era of industry 4.0. One of the efforts that the Faculty of Engineering will undertake to answer the challenges and opportunities is to hold a training on learning Programmable Logic Controller (PLC) which is a control device widely used in industry